UTILIZATION OF CORK AS COOLER BAG MAKING MATERIALS FOR DAIRY BREAST MILK AS AN EXCLUSIVE BREAST MILK COVERAGE ON WORKING MOTHER - Bina Melvia Girsang; Farida Linda Sari; Nur Afi Darti (Talenta Publisher, 2019)
Working mother factors, lack of knowledge about the benefits of breast milk, and the low support of assisting health workers are factors that influence the achievement of exclusive breast milk targets. The method of implementing community service activities was carried out with health counseling and assistance in the manufacture of milk bag milk milk cooler for 20 breastfeeding working mothers. Making cooler bags using cork as a material that is easily available and economical, is a breakthrough that can be made in helping to achieve exclusive breastfeeding programs. The purpose of this community service is to empower mothers through making cooler bags that are expected to improve the skills and confidence of working mothers in providing breast milk. The implementation of community service shows the results that mothers understand about the benefits of breast milk (80%), the statement of the attitude of mothers who are willing to milk breast milk in the workplace (80%), and all mothers are able to play a role in making cooler bags independently. Communities can learn independently (self learning) and can share experiences in preventing and tackling infant health, especially in fulfilling breast milk for infant growth and development